Spooky action at a distance? A two-phase study into learners’ views of quantum entanglement - Brang, Michael; Franke, Helena; Greinert, Franziska; Ubben, Malte S.; Hennig, Fabian; Bitzenbauer, Philipp (EPJ Quantum Technology, 2024)
Quantum entanglement is a challenging concept within the field of physics education, often eluding a full grasp by both educators and learners alike. In this paper, we report findings from a two-phase empirical study into the views of entanglement held by pre-service physics teachers and physics students from various universities. In the first phase, we utilized a questionnaire consisting of open-ended questions which was completed by 31 pre-service physics teachers. The study participants’ ideas were explored using qualitative content analysis which led to the creation of rating scale items used in study phase 2. These items were administered to a broader cohort including 73 physics university students in order to capture the learners’ agreement or disagreement with the questionnaire statements, and hence, helped to validate and substantiate the in-depth insights from study phase 1. Key findings revealed widespread accurate notions, like the need to consider the entire system when examining entangled states. However, less elaborated views were also identified, including ideas such as that measurements of entangled states always show perfect (anti-)correlation. Another striking observation was the confusion between quantum entanglement and superposition. In the case of quantum teleportation, many participants seemed to have a basic grasp of the concept, although a number of misconceptions were apparent, notably the idea that quantum entanglement enables faster-than-light communication. Practically, the findings can assist educators in anticipating and addressing widespread (mis-)conceptions, paving the way for more effective instruction in quantum mechanics and its real-world applications, such as quantum cryptography and computing.
CRIS-Team Scopus Importer:2024-05-17
Keywords: Empirical study; Entanglement; Quantum physics; Teleportation